Effect of different stunning methods on rigor mortis, shape, energetic status and physical characteristics of Salmo carpio fillets. (29th November 2022) - Pulcini, Domitilla; Pulido‐Rodríguez, Lina Fernanda; de Medeiros, Adja Cristina Lira; Faccenda, Filippo; Martini, Arianna; Martinoli, Marco; Tonachella, Nicolò; Secci, Giulia; Parisi, Giuliana
Abstract: BACKGROUND: Consumer interest in safeguarding animal welfare and increased demand for fresh aquatic products support the need to understand the effects of stunning methods used in aquaculture on the biochemical process affecting fish fillet quality. The present paper aimed at comparing electrical stunning (ES) and cold shock (ICE) in Salmo carpio, an Italian endemic under‐investigated species. Rigor mortis evolution, fillet adenosine 5′‐triphosphate (ATP), shape, colour, pH and water holding capacity were assessed by integrating chemical and image analyses. RESULTS: Seventy‐two fish (24 fish per treatment) were stunned by ES, ICE or anaesthesia (AN, used as control), then percussively slaughtered. ES and ICE hastened rigor mortis onset and resolution (21 and 28 h post mortem ) compared to AN. This was confirmed by the faster ATP degradation in ES and ICE. Fillet shape features varied during rigor mortis, according to the stunning method, with the perimeter showing irreversible variation in ES and ICE groups. Initial circularity was recovered only in AN, while ICE and ES fillets showed significantly different values, between 0 and 192 h. CONCLUSION: ES is a promising stunning technique for S. carpio, but parameters should be optimized, because of the adverse effect on muscle activity which caused a fast pH drop, and the presence of blood spots in the fillets. Further studies are needed to understand whether fillet shape changes can interfere with filleting or fillet processing and consumer appreciation. © 2022 Society of Chemical Industry.